IS THERE A MECHANISM FOR TAXING FOREIGN ECONOMIC ACTIVITY (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
Taxes serve as a crucial tool for the government to regulate and stimulate foreign economic activity. Therefore, as part of effective state control of foreign trade, improving the tax system for import-export activities is of great importance. According to a study by the magazine “Business Week”, over the past thirty years, international trade has contributed about 25% to global GDP growth, which emphasizes its importance. This importance is even more evident for Uzbekistan, where foreign trade provides 50-75% of technological advances and supplies a significant part of the necessary goods. Therefore, regulating export-import operations through tax policy is important.